Dysbiosis and colorectal cancer: conducive factors, biological and molecular role, and therapeutic prospectives - Gurkaranjot Singh; Zuhair Chaudhry; Anik Boyadzhyan; Kayvan Sasaninia; Vikrant Rai (Exploration of Targeted Anti-tumor Therapy)
Colorectal cancer (CRC) is the third leading cause of cancer-related death in the United States. Emerging evidence highlights the significant role of gut microbiota dysbiosis, characterized by a reduction in beneficial bacteria and an increase in pro-inflammatory and pro-carcinogenic bacteria, in CRC pathogenesis. Both genetic and environmental factors, including diet, antibiotic use, physical activity, aging, and obesity, contribute to this microbial imbalance. Dysbiosis promotes chronic inflammation and immune dysregulation, which facilitates tumor initiation and progression. This review examines the intricate interactions between gut microbiota, immune modulation, and CRC development. It explores current and emerging therapeutic strategies that target the microbiome to enhance treatment efficacy, discusses interventions aimed at restoring healthy microbiota in CRC patients, and outlines future directions for microbiome-based therapies to improve clinical outcomes.